Plurihormonal pituitary macroadenoma: a case report - Allehaibi, Ebtesam (J Med Case Rep, 2021)
BACKGROUND: Plurihormonal pituitary adenomas are a unique type of pituitary adenomas that secrete two or more pituitary hormones normally associated with separate cell types that have different immunocytochemical and ultrastructural features. Although they represent 10–15% of all pituitary tumors, only a small fraction of plurihormonal pituitary adenomas clinically secrete multiple hormones. The most common hormone combinations secreted by plurihormonal pituitary adenomas are growth hormone, prolactin, and one or more glycoprotein hormones. The most common hormonal symptom is acromegaly (50%). The aim of this case report is to bring awareness about this rare type of pituitary adenomas and to describe the unique presentation of our patient, even though plurihormonal pituitary adenomas are known mostly as a clinically silent tumors. CASE PRESENTATION: Herein, we describe an unusual case of plurihormonal pituitary adenoma with triple-positive staining for adrenocorticotropic hormone, growth hormone, and prolactin. The patient is a 65-year-old Egyptian woman who presented with mass effect symptoms of the pituitary tumor, which primarily manifested as severe headache and visual field defects. She also presented with some cushingoid features, and further analysis confirmed Cushing’s disease; slightly high prolactin and normal growth hormone levels were observed. She underwent transsphenoidal surgery and has been in remission thus far. Only a few cases have been reported in the literature, but none has exhibited silent acromegaly or mass effect symptoms as the initial presentation. CONCLUSION: This case highlights an unusual plurihormonal pituitary adenoma case with a rare combination of secreted hormones; mass effect symptoms were dominant, as were uncommon visual field defects. Our case further proves that immunohistochemical analyses of all pituitary hormones are needed to ensure correct diagnosis and to alert clinicians to the need for more rigorous follow-up due to the higher morbidity of these patients. Our case report approval number Federal Wide Assurance NIH, USA is FWA00018774 IRB registration number with OHRP/NIH is IRB00010471.